Perancangan Kayu Gelam Sebagai Sensor Pengukur Ketinggian Air untuk Mendukung Terwujudnya Green Electronics - Khairul Saleh; Iskhaq Iskandar; Assaidah (Jurnal Penelitian Pendidikan IPA, 2026)
The water level of peat land in the South Sumatra area required to be monitored for mitigating the wildfire or flooding annual risk happends in the region. The Gelam wood is easily found in the peat land thus the utilization as a water level sensor should be a perfect solution. Therefore, we designed a Gelam wood sensor as the sensing element, a voltage divider circuit as a transducer and a modem connected to a website to display the data for the user. The accuracy of the sensor is 98% with a resolution of about 1 cm in height. The system design was implemented to monitor the water level height of a campus lake and compared the output with a calibrated ultrasonic sensor. The reading error between both sensors was about 1.9%. Therefore, the use of Gelam wood as a water level measurement sensor can be developed towards the realization of 'green electronics' to obtain energy efficiency in producing an electronic component; eco-friendly and non-toxic materials thus it can reduce the electronic waste accumulated every year.